ARIMA FORECASTING OF THE PREVALENCE OF ANEMIA AMONG PREGNANT WOMEN IN NEPAL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Anemia is a common public health threat, especially in developing countries such as Nepal. Pregnant women in developing countries are even more vulnerable. Using annual time series data on the prevalence of anemia among pregnant women in Nepal from 1990 – 2018, the study seeks to make forecasts for the period 2017 – 2025. The study applies the BoxJenkins ARIMA methodology. The diagnostic ADF tests show that the AN series under consideration is an I (2) variable. Based on the AIC, the study presents the ARIMA (4, 0, 0) model [or the AR (4) model] as the optimal model. The residual correlogram indicates that the model stable. The results of the study show that there is likely to be a sharp rise in the prevalence of anemia in Nepal in pregnant women over the period 2017 to 2025, from the estimated 39.8% to about 42.3% by 2025. The study basically encourages the government of Nepal to intensify its support to pregnant women through the routine supplementations with iron and folate.